2019
DOI: 10.2147/ijn.s198194
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rifampicin conjugated silver nanoparticles: a new arena for development of antibiofilm potential against methicillin resistant<em> Staphylococcus aureus</em> and<em> Klebsiella pneumoniae</em></p>

Abstract: Background: Infections caused by drug resistant bacteria are a major health concern worldwide and have prompted scientists to carry out efforts to overcome this challenge. Researchers and pharmaceutical companies are trying to develop new kinds of antimicrobial agents by using different physical and chemical methods to overcome these problems. Materials and methods: In the present study, rifampicin conjugated silver (Rif-Ag) nanoparticles have successfully been synthesized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…The current results also revealed that the tested bacteria are highly sensitive to GL-AgNPs, BR-AgNPs, and SA-AgNPs, suggesting that the complex biofilm signaling mechanism could also be associated with cell survival. Recently, research has been conducted on conjugating the antibiotic, rifampicin, with chemically synthesized AgNPs for use in combatting biofilm formation by methicillin resistant S. aureus and Klebsiella pneumoniae (Farooq et al, 2019).…”
Section: Anti-biofilm Activity Of Agnpsmentioning
confidence: 99%
“…The current results also revealed that the tested bacteria are highly sensitive to GL-AgNPs, BR-AgNPs, and SA-AgNPs, suggesting that the complex biofilm signaling mechanism could also be associated with cell survival. Recently, research has been conducted on conjugating the antibiotic, rifampicin, with chemically synthesized AgNPs for use in combatting biofilm formation by methicillin resistant S. aureus and Klebsiella pneumoniae (Farooq et al, 2019).…”
Section: Anti-biofilm Activity Of Agnpsmentioning
confidence: 99%
“…Consistent with our results, previous studies have shown efficient effect of AgNPs in inhibiting biofilms produced by different microorganisms 70 , 71 . Different investigators have evaluated the ability of silver nanoparticles to inhibit biofilm formation by A. baumannii , Pseudomonas aeruginosa (synergy with tobramycin) , Staphylococcus aureus (such as synergy with vancomycin), Escherichia coli and Klebsiella pneumonia at similar concentrations 23 , 72 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Mohamed (2020) reported that AuNps conjugated with ampicillin/amoxicillin showed significant antibacterial activity and was biocompatible with treated cells. Farooq et al (2019) showed that rifampicin conjugated AgNps produced anti-biofilm activity against MRSA and K. pneumonia. Surwade et al (2019) reported that AgNps combined with ampicillin showed very strong synergistic effects against MRSA.…”
Section: Synergistic Antimicrobial Activity Of Nanoparticlesmentioning
confidence: 99%